Uma cidade entre sonhos de néon: encontros, transações e fruições com as culturas musicais urbanas contemporâneas - Guerra, Paula (2018)
This article derives from the theoretical and empirical developmentof the authors doctoral research on urban culturesand contemporary Portuguese music scenes, whichsought to demarcate and interpret the dynamics underlyingthe genesis, constitution and functioning of the subfieldof alternative rock in Portugal over the last 40 years.It focuses specifically on the cultural, artistic and musicalfruition of the cities of Oporto and Lisbon over the lastdecade, observing dissimilarities, persistences and specificities.This study confirmed the emergence of a Portugueseyouth framed in the sphere of aesthetic and playfulcosmopolitanism, bearer of a cosmopolitan cultural capital that is, a savoir-faire and savoir-vivre in the experimentationand enjoyment of cultural difference, through consumptionand urban musical, artistic and cultural practicesmarked by hybridity and eclecticism